Tourism Travel Agenda Planning Application Bengkulu City Based On Android - Ardoni, Yoan; Apridiansyah, Yovi; Wijaya, Ardi; Abdullah, Dedy (Penerbit Jurnal Indonesia, 2023)
Most of the tourists visiting the city of Bengkulu. constrained by a lack of access to information sources. Meanwhile, tourists also really need valid information about the place to be visited which results in a lot of wasted time searching for information related to the location of the object they want to visit. Based on this background, the researcher created an application called the Adroid-Based Tourism Travel Agenda Planning Application, which aims to assist tourists in determining destinations and assist tourists in arranging tourism itinerary scheduling. In conducting this research, the type of research used is qualitative research with a scientific approach and the system design method used is waterfall and for calculating the results of the questionnaire using quantitative methods. This application runs on Android-based smartphones. This application includes two contents namely destinations and agendas. Destination content has five features, namely, lodging, tours, souvenirs, and orders. The development of this application uses the Android Studio software. In modeling this application uses the UML method in the form of uses case digrams and is tested using the blackbox testing method. The results of testing this application conclude that the expected functions are all successful as expected. The conclusion is that the Bengkulu City Tourism Itinerary Planning Application can make it easier for tourists to find destination locations in Bengkulu City and help tourists plan travel agenda schedules with some of the information available on the application.